PERSEPSI SISWA TERHADAP DAYA JUANG MEREKA SERTA POLA ASUH ORANGTUA DAN GURU DI SD BERAKREDITASI A DAN C DI KABUPATEN BANTUL DAN BONE BOLANGO*) - Nur Listiawati (Jurnal Pendidikan dan Kebudayaan, 2016)
This study aims to examine students’ perception of their parents and teacher in instilling and developing students potential to improve their adversity quotient and students’ perception on their adversity quotient. This study is a case study carried out in two A and C accredited primary schools each in Bantul District and Bone Bolango District. Measurement of parenting used the inventory method. Measurement of students’ adversity quotient was conducted by the self-inventory method. Study result shows that accredited A primary school students’ perception on the parenting of parents and teachers and their adversity quotient in general are better than students’ perception of accredited C primary school. Parents cognitive abilities affect their ability to guide their children in analyzing and limit problems. The ability of teachers in the aspect of listening is lower than other aspects, namely, guiding to explore, analyze, and do something. Parenting from parents and teachers contribute to develope students adversity quotient significantly. However, it is only for few aspects such as guiding to explore, analyze, and do something that influenced. Even in sample schools located in Bantul, partially there is no aspect of teachers parenting that contributed to students adversity quotient. Perceptions of students in Bantul on their adversity quotient is generally higher than students in Bone Bolango.The study concludes that parents cognitive ability affect their ability to guide their child to analyze and isolate the problem. Growing and developing students’ adversity quotient will be more meaningful if collaboration between teacher and parents is improved. ABSTRAKStudi ini bertujuan untuk mengkaji pola asuh orang tua dan guru dalam menumbuhkan potensi daya juang siswa dan persepsi siswa terhadap potensi daya juang mereka. Studi ini merupakan studi kasus yang dilakukan di dua sekolah berakreditasi A dan C masing-masing di Kabupaten Bantul dan Kabupaten Bone Bolango. Pengukuran pola asuh orangtua dan guru menggunakan metode inventory. Pengukuran persepsi siswa terhadap potensi daya juang mereka dilakukan dengan metode self inventory. Hasil kajian menunjukkan bahwa secara umum persepsi siswa terhadap pola asuh orangtua dan guru serta daya juang siswa di sekolah berakreditasi A lebih baik daripada persepsi siswa di sekolah sampel berakreditasi C. Kemampuan kognitif orangtua memengaruhi kemampuan membimbing anak untuk menganalisis dan membatasi masalah. Kemampuan guru dalam aspek mendengarkan lebih rendah daripada aspek lainnya yakni membimbing untuk mengeksplorasi, menganalisis dan membatasi masalah, serta bertindak. Pola asuh orangtua dan guru memberikan kontribusi pada penumbuhkembangan potensi daya juang siswa. Namun, secara parsial hanya aspek membimbing untuk mengeksplorasi,menganalisa masalah, dan bertindak yang memengaruhi. Bahkan, pada SD sampel yang berada di Kabupaten Bantul secara parsial tidak ada aspek pola asuh guru yang berkontribusi secara signifikan pada penumbuhkembangan potensi daya juang siswa. Persepsi siswa di Kabupaten Bantul terhadap potensi daya juangnya secara umum lebih tinggi dibandingkan siswa di Kabupaten Bone Bolango. Studi ini menyimpulkan bahwa kemampuan kognitif orangtua memengaruhi kemampuan membimbing anak untuk menganalisis dan membatasi masalah. Penumbuhkembangan daya juang siswa lebih bermakna jika kolaborasi antara guru dan orangtua lebih ditingkatkan.